Markovian approach to stock price modelling in the Nigerian oil and gas sector - Adekunle S. Ayo; Eboigbe S. Uwabor (CBN Journal of Applied Statistics, 2021)
The study investigates the stock price movement of quoted Nigerian oil and gas firms using the Markovian model. Specifically, the study estimates the change in likelihoods and steady-state distribution of the share prices of the firms to determine the average time spent by the share price to move to another state and the turnover rate of the selected stocks. Markov chain-based stochastic modelling approach was employed by using the daily closing share prices of all the seven oil and gas firms quoted on the Nigerian Stock Exchange from April 2017 to January 2020. The study finds that the transition probabilities and the steady-state distribution of all the firms are stationary at first-order, implying that chain depends on the previous state. The steady-state probabilities of all the firms examined exhibit relatively high price stability in the long run. The study recommends that investors with diverse attitudes to risk-taking can explore the estimated long-run prospect of the investigated stocks in making guided investment decisions.
Keywords: C01; C02; C15; 330; Markov chain; oil and gas firms; share prices; stochastic process; transition probabilities